Metode Number Head Together untuk Meningkatan Motivasi dan Prestasi Belajar Tema 4 Sub Tema Globalisasi dan Manfaatnya pada Siswa Kelas VI MI Kunuzun Naja Purwoasri Kediri - Tyas, Elly Tria Febrining (Jurnal Simki Postgraduate, 2022)
To make changes in improving the quality and quality of education, the teacher plays a very important role because the teacher is the front person whose job is to transfer knowledge to students. For this reason, a strategy or learning method is needed which is carried out by the teacher and it really depends on the creativity of the teacher himself in conveying the contents of the material to students. Learning methods that do not involve students will reduce students' interest in learning, so that learning achievement will decrease. Numbered Heads Together type of cooperative learning is a type of cooperative learning that emphasizes a special structure designed to influence student interaction patterns and has the aim of increasing students' cognitive mastery. Based on the results of research data analysis and discussion, it can be concluded that the Number Head Together Method can increase learning motivation Theme 4 sub-themes of globalization and its benefits through the number head together method in class VI MI Kunuzun Naja Purwoasri Kediri odd semester 2022/2023 academic year of 20% of 71% in cycle 1 becomes 91% in cycle 2. The Number Head Together method can improve learning achievement Theme 4, the sub-theme of globalization and its benefits through the number head together method in class VI MI Kunuzun Naja Purwoasri Kediri odd semester of the 2022/2023 academic year which is shown with an increase in the percentage of classical completeness by 17.25 7% from 72.41% in cycle 1 to 89.66% in cycle 2. The increase in learning achievement was also indicated by an increase in the class average value of 8.83 from 74.83 in cycle 1 to 83.66 in cycle 2.